2015
DOI: 10.1021/acs.chemmater.5b01986
|View full text |Cite
|
Sign up to set email alerts
|

Local Structure of Rare-Earth Fluorides in Bulk and Core/Shell Nanocrystalline Materials

Abstract: NaREF 4 (rare-earth, RE = Y, Lu) nanocrystals (NCs) containing Ln 3+ -dopants are of great interest due to their unique ability to down-shift, downconvert and upconvert light. While the luminescent properties and microscale structures of such NCs are well understood, relatively little is known about their molecular-level structures, the nature of the NC cores and shells, and the interactions of the stabilizing ligands at the NC surface. To address these issues, we present a comprehensive characterization of bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 73 publications
(202 reference statements)
3
32
1
1
Order By: Relevance
“…To the best of our knowledge, the problem associated with the space group identification observed for bulk materials has only been discussed in the literature very recently for UCNCs. 24 Indeed, the recent study by Schurko and co-workers focusing on core-shell NaYF 4 -NaLuF 4 NCs (27 and 37 nm), was the first report on the structural problem related to β-NaLnF 4 UCNCs. 24 Schurko and co-workers concluded that !6 $ & ⁄ was the only space group compatible with their NMR data ( 23 Na, 19 F, 89 Y for the inorganic part).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, the problem associated with the space group identification observed for bulk materials has only been discussed in the literature very recently for UCNCs. 24 Indeed, the recent study by Schurko and co-workers focusing on core-shell NaYF 4 -NaLuF 4 NCs (27 and 37 nm), was the first report on the structural problem related to β-NaLnF 4 UCNCs. 24 Schurko and co-workers concluded that !6 $ & ⁄ was the only space group compatible with their NMR data ( 23 Na, 19 F, 89 Y for the inorganic part).…”
mentioning
confidence: 99%
“…24 Indeed, the recent study by Schurko and co-workers focusing on core-shell NaYF 4 -NaLuF 4 NCs (27 and 37 nm), was the first report on the structural problem related to β-NaLnF 4 UCNCs. 24 Schurko and co-workers concluded that !6 $ & ⁄ was the only space group compatible with their NMR data ( 23 Na, 19 F, 89 Y for the inorganic part). Note that the authors only considered !6 $ & ⁄ and !6 # 2& as possible space groups; yet, historically, the confusion was between !6 # and !6 $ & ⁄ .…”
mentioning
confidence: 99%
“…As for the 19 F MAS‐NMR spectra (Figure f), fluorine in the Al‐F‐Na bonds at –190 ppm always exists before/after glass crystallization, implying that a part of F − and Na + ions in glass are actually confined within the Al‐F‐Na groups and may not contribute to the crystallization of NaYF 4 . Resonance bands in the range from –160 ppm to 50 ppm are attributed to fluorine in the (α&β) NaYF 4 crystals, where significant changes in resonance positions and spectral shapes from GC1 to GC6 are detected due to α→β phase transition of the precipitated NaYF 4 . Worthy of notice, the similar F − resonance case in PG to that in GC1 further confirms the presence fluoride‐rich domains, which is believed to act as nucleation centers to promote NaYF 4 crystallization.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, heterostructured core-shell nanomaterials can possess improved or new properties when compared with either the core or the shell materials. Among diverse heterostructured core-shell nanomaterials, lanthanide doped upconversion nanoparticles with core-shell heterostructures, which can convert two or more low-energy photons into highenergy photons, recently have received considerable attention because of their merits and promising applications 6,[8][9][10][11][12][13][14][15][16][17] . Specifically, heterostructured core-shell upconversion nanoparticles can improve the luminescent properties of conventional upconversion nanoparticles, giving strong and tunable upconversion emission 9,18 .…”
Section: Introductionmentioning
confidence: 99%